2004
DOI: 10.1088/0031-9155/50/2/001
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution PET detector design: modelling components of intrinsic spatial resolution

Abstract: The development of dedicated small animal PET (positron emission tomography) scanners has led to significantly higher spatial resolution and comparable sensitivity to clinical scanners. However, it is not clear whether we are approaching the fundamental limit of spatial resolution. This work aims to understand what is currently limiting spatial resolution during data formation and collection and how to apply that knowledge to obtain the best possible resolution for small animal PET without sacrificing sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 27 publications
4
107
0
2
Order By: Relevance
“…3C). Feasibility studies focusing on small crystals for PET detectors have shown that, in theory, the smallest achievable resolution is on the order of 0.4 mm in the reconstructed image (33). However, resolutions beyond that are unlikely because the intrinsic physical limitations, such as positron range and noncolinearity of the annihilation g-photons, will dominate.…”
Section: Pet Advances In Pet Detector Technologymentioning
confidence: 99%
“…3C). Feasibility studies focusing on small crystals for PET detectors have shown that, in theory, the smallest achievable resolution is on the order of 0.4 mm in the reconstructed image (33). However, resolutions beyond that are unlikely because the intrinsic physical limitations, such as positron range and noncolinearity of the annihilation g-photons, will dominate.…”
Section: Pet Advances In Pet Detector Technologymentioning
confidence: 99%
“…Thus in PET, relevant models include -among others-geometric sensitivity, positron range, photon pair non-colinearity, Compton scatter in tissues, detector sensitivity, inter-crystal scatter and penetration and detector dead-times. Additionally, one may have some statistical models Interestingly, system modeling plays a very important role in ET for optimizing detector design, configuration and materials (see Levin & Zaidi (2007) and Stickel & Cherry (2005)) 2 and for assesing acquisition and processing protocols, for example to study differences in image quality when using radionuclides with various positron ranges (Bai et al (2005)) or properties that are not possible to measure directly like the behavior of scattered photons (Dewaraja et al (2000)). Likewise, it is also a valuable tool in the design and assessment of correction and reconstruction methods (Zaidi & Koral (2004), Holdsworth et al (2002)) and in the study of an imaging system response (Alessio et al (2006)).…”
Section: System Modeling and Simulationmentioning
confidence: 99%
“…For the most commonly used positron emitters (F, C), this average distance is on the order of 0.5 mm or less. This positron range effect poses a lower limit to the spatial resolution with PET, achievable without the use of sophisticated mathematical models (11)(12)(13)(14). Because every measurement with PET is composed by a large number of annihilations, some of the lost spatial resolution can be recovered with appropriate data treatment that estimates the expected location of origin (10,11).…”
Section: Principles Of Pet and Spectmentioning
confidence: 99%